Distribution Pattern of Micronutrients in Relation to Soil Properties in Pipli and Thanesar Blocks of Kurukshetra - Dikshant Sheoran; R.S. Garhwal; Karuna (Journal of the Indian Society of Soil Science, 2026)
A detailed study of spatial variations in soil fertility is essential for implementing precise and sustainable nutrient management practices. The present study was carried out soil micronutrients status of Pipli and Thanesar blocks of Kurukshetra district, Haryana using geographic information system (GIS) and global positioning system (GPS). A total of 220 geo-referenced soil samples were collected from a depth of 0–15 cm across 110 villages, and the data was analysed and mapped using GIS tools (ArcGIS 10.2). The soils in both blocks were found to be neutral to alkaline in reaction and non-saline in nature. The mean concentrations of available micronutrients in the Pipli block were 1.79 mg kg-1 for Zn, 8.49 mg kg-1 for Fe, 1.34 mg kg-1 for Mn, and 3.51 mg kg-1 for Cu. Corresponding values in the Thanesar block were 1.90 mg kg-1 (Zn), 7.67 mg kg-1 (Fe), 1.04 mg kg-1 (Mn), and 3.39 mg kg-1 (Cu). While the levels of manganese were consistently sufficient across all samples, other micronutrients exhibited spatial variability. No significant correlation was observed between the availability of these micronutrients and soil pH or electrical conductivity. These findings underscore the importance of localized soil fertility assessments for precision nutrient management strategies.